Intersecting Realities: Body Dysmorphic Disorder and Substance Abuse in Women – A Holistic Treatment Approach - Metin Çınaroğlu (Sakarya Üniversitesi Kadın Araştırmaları Dergisi)
The intersection of Body Dysmorphic Disorder (BDD) and substance abuse in women presents a clinical tableau rich with complexity and challenges. This review explores the intricate relationship between BDD—a disorder characterized by an obsessive preoccupation with perceived physical flaws—and substance abuse, where women may turn to drugs or alcohol as a maladaptive coping mechanism to alleviate the distress associated with BDD. A literature-focused methodology was employed in the study. In this context, databases such as PubMed, DergiPark, WoS, and ScienceDirect were utilized to explore the relevant literature. The analysis delves into the unique manifestation of BDD in women, influenced by societal, cultural, and psychological factors that often impose stringent beauty standards and exacerbate body image concerns. Patterns of substance abuse among women are discussed, highlighting the rapid progression from usage to dependency, known as telescoping, and the impact of societal stigma that compounds the struggles of women with addiction. Risk factors for both conditions are examined, with a focus on shared contributors such as trauma, mental health comorbidities, and societal pressures. Current treatment approaches are reviewed, advocating for an integrated model that combines psychotherapy, pharmacotherapy, and holistic or alternative interventions. The review emphasizes the importance of Cognitive Behavioral Therapy for BDD and Medication-Assisted Treatment for substance abuse, as well as the inclusion of mindfulness, meditation, and gender- The conclusion reinforces the imperative of a cohesive treatment strategy, underscoring the need for gender-specific, trauma-informed care that understands and addresses the complex interplay between BDD and substance abuse in women. This comprehensive approach promises more effective support and a hopeful pathway to recovery for women entangled in the web of these co-occurring disorders.